Immunological synapse formation as a key mechanism in T cell-dependent bispecific antibody-mediated immune activation and cytotoxicity - Rikuto Nakamura; Ryo Tsumura; Takahiro Anzai; Ryutaro Asano; Masahiro Yasunaga (Cancer Immunology, Immunotherapy)
Abstract T cell-dependent bispecific antibodies (TDBs) are next-generation antibody therapies that link cancer cells and T cells to achieve potent antitumor effects. Despite the successful development of TDBs for hematological malignancies, their efficacy against solid tumors remains limited. Overcoming this challenge requires a deeper understanding of their mechanisms of action. While the basic process of immunological synapse (IS) formation and T cell activation by TDB is known, the detailed effects of IS on the bystander effect and T cell migration, both crucial for therapeutic efficacy, remain unclear. This study investigated these mechanisms using an EGFR/CD3 TDB (hEx3) and EGFR knockout cancer cells (KO). The results revealed that IS formation by TDB induced a bystander effect, leading to damage in surrounding KO, with the extent depending on the proportion of EGFR-positive wild-type cancer cells (WT) and the duration of co-culture. Furthermore, IS formation significantly enhanced T cell cytokine and chemokine secretion, promoting T cell migration. These findings provide critical insights into TDB efficacy mechanisms and highlight the importance of evaluating IS formation in developing new antibody drugs. Establishing a reliable system for assessing IS formation will be essential for advancing TDBs and other antibody-based therapies, particularly against solid tumors.